Effect Of Job Satisfaction on Work Discipline Of Employees On Cargo Company - Nurhayana (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2021)
This study aims to determine the effect of job satisfaction on employee work discipline. The sample in this study were all employees, totaling 40 employees who were used as research samples. The results of SPSS in this study obtained test results on the variable Job Satisfaction Against Work Discipline, namely t count (7,500) > t table (2,024). And the significance level obtained is 0.00 <0.05 so it can be concluded that job satisfaction has a significant effect on employee work discipline. The value of R-square (Coefficient of Determinants) is 0.597. It can be concluded that job satisfaction affects the work discipline of PT ABC Cargo Company Pekanbaru Branch by 59.70%.